Temporal variation of the shallow subsurface at the Aquistore CO2 storage site associated with environmental influences using a continuous and controlled seismic source. Issue 4 (12th April 2017) - Ikeda, Tatsunori; Tsuji, Takeshi; Takanashi, Mamoru; Kurosawa, Isao; Nakatsukasa, Masashi; Kato, Ayato; Worth, Kyle; White, Don; Roberts, Brian
Abstract: The development of reliable systems for monitoring injected CO2 is essential in carbon capture and storage projects. We applied time‐lapse surface wave analysis to measure temporal variations of the shallow subsurface among 11 periods (0.2–21.6 days) of continuous seismic data acquired from 2014 to 2016 at the Aquistore CO2 storage site in Canada. We focused on monitoring environmental influences on shallow seismic velocity, which are unrelated to CO2 injection into deep reservoirs. A continuous, controlled seismic source system called Accurately Controlled Routinely Operated Signal System was used to enhance the temporal resolution and source repeatability. Observed phase velocities were clearly higher in winter than in warmer seasons. The seasonal variation could be reproduced by an increase in the shallow S wave velocity during winter associated with the greater extent of freezing of partially saturated rock. We also observed gradual increases or decreases in phase velocities as the seasons changed, which could be related to gradual freezing or melting of ice. Our monitoring system thus could be effective for monitoring temporal variations of the shallow subsurface associated with the degree of freezing. Furthermore, the high temporal stability of our monitoring approach in warm seasons may make it possible to immediately identify CO2 leakage in the shallow subsurface. Key Points: We monitored the shallow subsurface at the Aquistore CO2 storage site using the ACROSS source system We estimated near‐surface S wave velocity variations possibly related to changes in the degree of freezing of partially saturated rock High temporal stability of our monitoring approach may make it possible to immediately identify CO2 leakage in the shallow subsurface